Fray Antonio de la Calancha and the Languages of the North Coast of Peru: The Question of Sec and the Languages of the Tallanes - Arrizabalaga Lizarraga, Carlos (2024)
This paper reviews the inconsistencies that historiography has shown about the identification of names and the delimitation of   the  extension  of   the  languages  that  were  spoken  in  the  regions  of   Piura  and  Tumbes,  in  northern  Peru,  and  the  in-fluence that some ideas have had on the claiming a regional identity  based  on  a  diffuse  but  powerful  idea  of       an  ancient  Tallan  nation  that  would  have  extended  its  dominance  over  the warm sands of  this western end of  South America. From the review of  historiography, it is possible to determine that the  term  «lengua  sec»  has  been  confusedly  attributed  to  the  tallanes,  based  on  a  misreading  of   the  chronicle  of   Antonio  de la Calancha by Luis E. Valcárcel, supported by a late work by Clements R. Markham.